2023
DOI: 10.21203/rs.3.rs-2424871/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disrespect during childbirth and postpartum mental health: a French cohort study

Abstract: Background: While the World Health Organisation (WHO) warned about disrespect and abuse during childbirth as early as 2014. This same year a social media movement with #payetonuterus brought to light the problematic of obstetrical violence in French speaking countries. The experience of care is an integral part of the quality of care, and perception on inadequate support during labour and loss of control in labour are some of the most frequently reported risk factors for childbirth-related post-traumatic stres… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Numerous studies conducted by midwives have shown that the organization of care impacts practices and women's health. This includes various aspects such as pain management during labor, interventions in postpartum hemorrhage, reorganization of midwifery care during the COVID pandemic, or simply listening to women's childbirth preferences [21][22][23][24]. Finally, research on midwifery pedagogy should also expand in the future [25,26].…”
Section: Midwivesmentioning
confidence: 99%
“…Numerous studies conducted by midwives have shown that the organization of care impacts practices and women's health. This includes various aspects such as pain management during labor, interventions in postpartum hemorrhage, reorganization of midwifery care during the COVID pandemic, or simply listening to women's childbirth preferences [21][22][23][24]. Finally, research on midwifery pedagogy should also expand in the future [25,26].…”
Section: Midwivesmentioning
confidence: 99%